1997
DOI: 10.1037/0021-843x.106.4.649
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypy in community samples: The three-factor structure and correlation with sustained attention.

Abstract: The authors examined cross-cultural applicability of the Schizotypal Personality Questionnaire (SPQ), the Perceptual Aberration Scale (PAS), and the Continuous Performance Test in community samples of Taiwanese adults and adolescents. The authors tested hypotheses that a 3-factor structure of the SPQ (Cognitive-Perceptual, Interpersonal, and Disorganization: A. Raine et al., 1994) exists for both samples and that the Interpersonal factor is associated with poorer attention. The authors replicated the 3-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
176
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 240 publications
(207 citation statements)
references
References 27 publications
(58 reference statements)
26
176
5
Order By: Relevance
“…Other studies have confirmed that simpler 1-factor and 2-factor models do not provide good fit to the data (Chen et al, 1997;Raine et al, 1994;Reynolds et al, 2000;Stefanis et al, 2004;Wuthrich and Bates, 2006). Although it could be suggested that the present findings supporting the 4-factor model of Stefanis et al (2004) are due to close similarities between the current sample and theirs, this is an unlikely sole explanation given that other factor analytic studies (e.g., Raine et al, 1994;Wuthrich and Bates, 2006) were conducted with English-speaking undergraduate samples similar to the one used in this study.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Other studies have confirmed that simpler 1-factor and 2-factor models do not provide good fit to the data (Chen et al, 1997;Raine et al, 1994;Reynolds et al, 2000;Stefanis et al, 2004;Wuthrich and Bates, 2006). Although it could be suggested that the present findings supporting the 4-factor model of Stefanis et al (2004) are due to close similarities between the current sample and theirs, this is an unlikely sole explanation given that other factor analytic studies (e.g., Raine et al, 1994;Wuthrich and Bates, 2006) were conducted with English-speaking undergraduate samples similar to the one used in this study.…”
Section: Discussioncontrasting
confidence: 49%
“…Items are grouped into nine subscales reflecting the DSM SPD criteria. As shown in Table 1, Cronbach's (α) internal consistency reliability coefficients for these subscales ranged .70-.83 (mean=.75) in the present sample, exceeding the means of .65 and .69 reported by Chen et al (1997) for adults and adolescents, respectively. Scores to measure three domains of schizotypy are typically derived by simple summation of subscale scores: the cognitive-perceptual domain (ideas of reference, odd beliefs or magical thinking, unusual perceptual experiences, and paranoid ideation/suspiciousness subscales); the interpersonal domain (excessive social anxiety, no close friends, constricted affect, and paranoid ideation/suspiciousness subscales); and the disorganized domain (odd or eccentric behavior and odd speech subscales).…”
Section: Methodsmentioning
confidence: 65%
See 3 more Smart Citations